Scanning Electron Microscopic Studies on Uterus of Jaffarabadi Buffalo during Follicular and Luteal Phases of Estrous Cycle - Kumar, Vishnu Deo; Vyas, KN; Tank, PH; Sharma, Ani; Talekar, SH (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The study was conducted on uterus of 20 adult Jaffrabadi buffaloes. Scanning electron microscopic observation showed that the surface of endometrium was folded. Lining epithelium of horn and body consist of ciliated and nonciliated cells. During follicular phase cells were flat, formed hexagonal structure with numerous microvilli, whereas, cells were narrow and polygonal in shape during luteal phase. More number of well-developed ciliated cells were found in follicular phase as compared to luteal phase. Numerous secretory blabs were observed on surface of secretory cells during luteal phase. The folds in the cervix were narrow and deep. The lining epithelium of cervix had ciliated and nonciliated cells. The cilia were more in cranial part than the caudal part of the cervix and present in the form of bunch, which were overlapping the secretory cells. Ciliated cells were more in number during follicular phase. Cervical glands were distributed on the cervical mucosa and ciliated cells were present around the openings of these glands. involved in sperm transport, implantation, In mammals, the endometrium of the uterine horns plays a critical role in normal fertility and also represents different features in order to adapt through various phases of estrus cycle. The uterus not only has an influence on ovarian structure but also can participate in different physiological events by producing uterine milk. Therefore, it can provide an appropriate environment for sperms and blastocyst. Finally, the implantation process can be done completely (Shahrooz et al., 2013). Generally, the most important function of the uterus in ruminant is pregnancy and parturition which is associated with adjustment of cellular structures and microenvironments (Barnes, 2000). To better understand the basic structure and physiology of the buffalo uterus, more information is needed regarding the differences between the segments associated with the stages of estrus cycle. Therefore, the aim of the present study was to investigate the follicular and luteal phases of estrus cycle in the uterus of Jaffarabadi buffalo through the scanning electron microscopic approaches.
Keywords: Follicular phase; Luteal phase; Jaffarabadi buffalo; Uterus; SEM.